Galleria Continua : Le Moulin. - Bernini, Isabelle; Ferrand, Mylène; Fiaschi, Lorenzo (Beijing San Gimignano : Galleria Continua San Gimignano, 2007)
De Bruyckere, Berlinde ; Buren, Daniel ; Cai Guo-Qiang ; Cariello, Letizia ; Cecchini, Loris ; Chen Zhen ; Gu Dexin ; Fulgeri, Marina ; Gaba, Meschac ; Garaicoa, Carlos ; Geers, Kendell ; Hatoum, Mona ; Kabakov, Ilya ; Kapoor, Anish ; Liu Jianhua ; Macchi, Jorge ; Mezzaqui, Sabrina ; Morgantin, Margherita ; Nasr, Moataz ; Op de Beeck, Hans ; Orta, Lucy ; Ozzola, Giovanni ; Pancrazzi, Luca ; Peinado, Bruno ; Pistoletto, Michelangelo ; Sedmach, Manuela ; Serse ; Solakov, Nedko ; Tayou, Pascale Marthine ; Vanzo, Marcella ; Ai Weiwei ; Xuan, Kan ; Yan Lei ; Zheng Guogu ; Zhuang Hui
Engels
Italiaans
boek